Improper solid waste management at the Duala market, Monrovia-Liberia - Gabriel Zean; Fuad Muhammad; Budi Warsito (BIORE Scientia Publisher, 2023)
The population of Monrovia is increasing accompanied by rapid urbanization. Due to rapid urbanization, economic development, higher living standards, and changes in consumption patterns and lifestyle, the generation rate of waste has increased. Mismanagement of solid waste tends to hinder any progress toward environmental sustainability. This study endeavored to determine Improper Solid Waste Management at the Duala Market, Monrovia-Liberia examines the connection between population growth, economic development, and the rise in waste production. The study evaluated behavioral factors on a qualitative and quantitative level, including knowledge, attitude, and practices of solid waste management, stakeholder collaboration, and obstacles to sustainable waste management in Monrovia. To display the various socioeconomic groups in the city, households were chosen at random (simple and stratified). The key findings revealed socio-demographic (70%) Waste generated are inadequately disposed of by female, as a result of the large fragment of waste that is still not collected, waste is dumped and burned in the open. followed by intervention to reduce improper waste management accounts (40%) which need public awareness and factors leading to improper waste management accounts (30%), not cognizant of the waste management area. These waste management challenges have become heightened because of insufficient technology to ensure proper management and low budgetary allocations for effective waste management.